Optimization of PV Power Capacity of 10 KWp Capacity Based on P&O Algorithm and Boost Converter - Rajagukguk, Antonius; Aritonang, Maryani (Electrical Engineering Department, Faculty of Engineering, Universitas Riau, 2020)
Using solar panels as a power plant can reduce the dependence of fuel oil. To work always on maximum power points (MPP), Photovoltaic (PV) requires optimization method. Therefore, the authors are interested in discussing the optimization method of the PV array model using Maximum Power Point Traking (MPPT) with the Perturbation & Observation (P & O) Algorithm and Boost Converter. In this case, PV capacity will be simulated on 10 kWp. That PV consists of 4 strings, which is each strings consist of 10 PV modules. The output of PV modules will be forwarded to the Boost Converter circuit. Boost Converter want is controlled by P&O Algorithm. The voltage and current generated from the PV array modeling will be used by the P&O Algorithm as a reference. The function of P&O Algorithm is to track the Maximum Power Point (MPP) of the PV model. The result of tracking power by P&O Algorithm will be forwarded to Pulse Width Modulation (PWM) circuit as a duty cycle generator. Duty cycle signal will be forwarded to the switching tool contained in the converter circuit. By that control system, PV model expected has maximum power according to the voltage. Based on the results of power test by 1000 W/m2 radiation, maximum power obtained is equal to 9967 Wp with 99.6 % efficiency at a voltage level of 400 volt. Therefore,it can be concluded that the design of the PV Array System using P&O Algorithm and the Boost Converter can work well.